MMP13 mutation causes spondyloepimetaphyseal dysplasia, Missouri type (SEMD(MO). - Kennedy, A; Inada, M; Krane, S; Christie, P; Harding, B; López-Otín, C; Sánchez, L; Pannett, A; Dearlove, A; Hartley, C; Byrne, M; Reed, A; et al. (2005)
MMPs, which degrade components of the ECM, have roles in embryonic development, tissue repair, cancer, arthritis, and cardiovascular disease. We show that a missense mutation of MMP13 causes the Missouri type of human spondyloepimetaphyseal dysplasia (SEMD(MO)), an autosomal dominant disorder characterized by defective growth and modeling of vertebrae and long bones. Genome-wide linkage analysis mapped SEMD(MO) to a 17-cM region on chromosome 11q14.3-23.2 that contains a cluster of 9 MMP genes. Among these, MMP13 represented the best candidate for SEMD(MO), since it preferentially degrades collagen type II, abnormalities of which cause skeletal dysplasias that include Strudwick type SEMD. DNA sequence analysis revealed a missense mutation, F56S, that substituted an evolutionarily conserved phenylalanine residue for a serine in the proregion domain of MMP13. We predicted, by modeling MMP13 structure, that this F56S mutation would result in a hydrophobic cavity with misfolding, autoactivation, and degradation of mutant protein intracellularly. Expression of wild-type and mutant MMP13s in human embryonic kidney cells confirmed abnormal intracellular autoactivation and autodegradation of F56S MMP13 such that only enzymatically inactive, small fragments were secreted. Thus, the F56S mutation results in deficiency of MMP13, which leads to the human skeletal developmental anomaly of SEMD(MO).